Judicial Review of Administrative Decisions in Vietnam: Insights from the Chevron Doctrine - Trang, Nguyen Thu (VNU Journal of Science: Legal Studies; Vol 41 No 1DO - 10.25073/2588-1167/vnuls.4637, 2025)
Judicial review of administrative decisions is a crucial mechanism for ensuring the rule of law in state management. In the context of building a socialist rule of law state, Vietnam faces significant challenges in determining the scope and extent of judicial intervention in administrative decisions. The formation, development, and termination of the Chevron doctrine in the United States provides valuable experiences on balancing respect for administrative expertise with effective judicial review. This study analyzes the core principles of the Chevron doctrine to draw insights for improving Vietnam's judicial review mechanism, focusing on three aspects: recognizing and controlling administrative discretion; achieving a reasonable balance between the expertise of administrative agencies and the effectiveness of judicial review by the courts; expanding the scope of judicial review. In doing so, the study contributes to building an effective judicial review mechanism, serving the goal of developing the Vietnamese socialist rule-of-law state.